Coperative Rural Development Trust Paves the path for sustainable rural development - Prasad, Manbodh (Indian Farming, 2017)
The Cooperative Rural Development Trust of IFFCO provides practical training to the farmers through their various rural development programmes. The trust helps to improve the skills of farmers in various agricultural activities and plays a big role in their upliftment.